Science Communication for Children in Public Televiison (2019)
Gabriel E. Levy B makes a deep reflection based on an investigation of the content presented by television in Colombia and its approaches, also raises the issue of technological instruments in schools and educational space. He ends by reflecting on the importance of presenting children with content of good warmness, well thought out for their education and amusement